Anatomical course, variations and radiological evaluation of injury to cadaveric lingual nerve / Samah Mohammed Abdulla al-Amery - Samah Mohammed, Abdulla al-Amery (2017)
The lingual nerve injury is a serious neurological complication which may interfere with the patient’s daily activity, and adversely affect the psychological state of the patient. Aims: This study has three aims: (1) To determine the anatomical course and potential variations that may contribute to lingual nerve injury, (2) Assess the effectiveness of the ultrasonography and magnetic resonance imaging (MRI) in detecting bur injury with reference to optical coherence tomography (OCT) images, and (3) Compare the amount of damage of the lingual nerve caused by using two different surgical burs. Materials and Methods: This cadaveric research involved the study of 14 hemi-mandibles for: (a) obtaining morphometrical measurements of the lingual nerve position to three landmarks on the alveolar ridge, and (b) determining the number of terminal branches inserting in the ventral surface of the tongue. In the subsequent part of the study, twelve lingual nerves were exposed to injury using two different types of burs (Carbide bur and Dentium bur). The amount of damage caused by the two burs was first measured using OCT. Subsequently, the same lingual nerves were scanned with ultrasound and MRI to assess their capability in detecting the lingual nerve injury. Result: The mean distance between the twelve lingual nerves and the alveolar ridge was 12.32 mm, and they were located 11.82 mm from the lower border of the mandible. These distances were varied when near the first molar (M1), second molar (M2) and third molar (M3). The lingual nerve coursed on the floor of the mouth for approximately 25.17 mm before it deviated toward the tongue anywhere between the mesial of M1 and distal of M2. Eleven lingual nerves were found to loop around the submandibular duct for an average distance of 6.91 mm. Their looping occurred anywhere between the M2 and M3. In 72.7% of the cases the loop started around the M3 region while it mostly ended at between M1-M2 (63.6%). The lingual nerve gave out as many as 4 branches at its terminal end to insert in the ventral surface of the tongue, with 2 branches being the most common pattern. With regards to damage caused by surgical burs, at high speed (1500 rpm), the Dentium bur caused deeper [0.22 (SE 0.04) mm] and wider [1.87 (SE 0.25) mm] laceration than the Carbide bur. Statistically there was no significant different between the OCT recording of damage and the ultrasound reading, while the MRI failed to detect the lingual nerve. Conclusion: An awareness of the variations of the lingual nerve is important to prevent any untoward complications or nerve neuropathy. In addition, it appears to be more favorable to use a Carbide bur for surgical procedure (preferably at a low speed) as it minimizes damage to the lingual nerve. The ultrasound scanning capability in detecting the lingual nerve injury would provide an objective evaluation for the amount of nerve damage in-vivo. It is hoped that these findings will be useful for planning surgical procedures in the posterior floor of the oral cavity.